Fluorescent Antibody Technique For Detection Of Salmonella Typhimurium In The Intestine Of Experimentally Infected Calves: Faisal, G. Habasha and Abdul Wahab Abul Razak - Habasha, Faisal G. (The Iraqi Journal of Veterinary Medicine, 2008)
A systemic study on the pathogenesis of experimentally inducedSalmonella typhimurium infection was carried out in calves. Sixteen normal,colostrum-fed, friesian calves, ranging in age from 3 to 6 weeks were used. Thecalves were divided into two equal groups. Group I calves were inoculatedorally with 1.5 x 1011 CFU of Salmonella typhimurium and group II calvesserved as control.Using an indirect fluorescent antibody technique, it was found thatSalmonella typhimurium has an apparent predilection for the small intestineparticularly jejunum and ileum. The results of this study suggest that thistechnique can be considered as a rapid reliable technique for diagnosis ofsalmonellosis in endemic outbreaks.